2018
DOI: 10.1111/jocs.13715
|View full text |Cite
|
Sign up to set email alerts
|

Radical pericardiectomy for chronic constrictive pericarditis

Abstract: Radical pericardiectomy provided superior 10-year survival and clinical functional improvement in patients with chronic constrictive pericarditis compared to sub-total pericaridectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
25
0
5

Year Published

2019
2019
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 19 publications
3
25
0
5
Order By: Relevance
“…The surgical methods are classified as complete pericardiectomy and partial pericardiectomy according to the extent of pericardial resection. Complete pericardiectomy has been proven to be not only associated with lower perioperative mortality [9] but also confer significant long-term survival benefit and clinical functional improvement [10,18]. Generally, pericardiectomy can be performed through either median sternotomy or left anterolateral thoracotomy, while median sternotomy provides adequate exposure of the right atrium, right ventricle and the vena cava, thus enabling extensive pericardial resection [19].…”
Section: Discussionmentioning
confidence: 99%
“…The surgical methods are classified as complete pericardiectomy and partial pericardiectomy according to the extent of pericardial resection. Complete pericardiectomy has been proven to be not only associated with lower perioperative mortality [9] but also confer significant long-term survival benefit and clinical functional improvement [10,18]. Generally, pericardiectomy can be performed through either median sternotomy or left anterolateral thoracotomy, while median sternotomy provides adequate exposure of the right atrium, right ventricle and the vena cava, thus enabling extensive pericardial resection [19].…”
Section: Discussionmentioning
confidence: 99%
“…In order to reduce the incidence of postoperative complication and death, some studies have attempted to nd the possible risk factors to improve the strategies of perioperative management. The extent of pericardial resection was one of the risk factors and complete pericardiectomy was associated with superior surgical outcomes to partial pericardiectomy [16,23,24] . Cardiopulmonary bypass was also a predictor of poor prognosis and the 30-day mortality rate might reduce without the use of cardiopulmonary bypass [25] .…”
Section: Discussionmentioning
confidence: 99%
“…Pericardiectomy is the only definitive treatment for established constriction, and most studies suggest that resection should be as complete as technically feasible [49,[54][55][56][57]. A retrospective review by Nozohoor et al showed that radical pericardiectomy was associated with improved functional status and 10-year survival rates of 94% compared to 55% with subtotal pericardiectomy [55]. Bozbuga et al also showed that performing early radical resection in combination with appropriate chemotherapeutic agents translated into the best outcomes in patients with tuberculous disease [56].…”
Section: Pericardiectomy For Constrictive Pericarditismentioning
confidence: 99%
“…Pericardial stripping is carried out via sternotomy or lateral thoracotomy with or without cardiopulmonary bypass support [49]. Total resection is extremely difficult to perform via a thoracotomy, and median sternotomy is the preferred approach to provide definitive resection and optimise benefit [49,55].…”
Section: Types Of Pericardiectomymentioning
confidence: 99%
See 1 more Smart Citation